2016
DOI: 10.1016/j.cub.2016.04.054
|View full text |Cite
|
Sign up to set email alerts
|

Direct Two-Dimensional Access to the Spatial Location of Covert Attention in Macaque Prefrontal Cortex

Abstract: Direct access to motor cortical information now enables tetraplegic patients to precisely control neuroprostheses and recover some autonomy. In contrast, explicit access to higher cortical cognitive functions, such as covert attention, has been missing. Indeed, this cognitive information, known only to the subject, can solely be inferred by an observer from the subject's overt behavior. Here, we present direct two-dimensional real-time access to where monkeys are covertly paying attention, using machine-learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
119
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(137 citation statements)
references
References 29 publications
18
119
0
Order By: Relevance
“…14 Converging evidence demonstrate that the prefrontal cortex (PFC) is at the origin of the attentional control 15 signals underlying the behavioral attentional spotlight 7,[14][15][16][17] . Supporting this idea, we recently 16 demonstrated that this attentional spotlight can be reconstructed and tracked from PFC neuronal 17 population activity with a very high spatial and temporal resolution 18,19 . However, recent experimental 18 work provides a completely different perspective onto selective attention, suggesting that spatial 19 attention samples the visual scene rhythmically [20][21][22][23][24][25][26] .…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…14 Converging evidence demonstrate that the prefrontal cortex (PFC) is at the origin of the attentional control 15 signals underlying the behavioral attentional spotlight 7,[14][15][16][17] . Supporting this idea, we recently 16 demonstrated that this attentional spotlight can be reconstructed and tracked from PFC neuronal 17 population activity with a very high spatial and temporal resolution 18,19 . However, recent experimental 18 work provides a completely different perspective onto selective attention, suggesting that spatial 19 attention samples the visual scene rhythmically [20][21][22][23][24][25][26] .…”
Section: Introductionmentioning
confidence: 91%
“…The above described analyses were performed on a quantification of the accuracy with which attention 234 could be localized in one of the four visual quadrants, based on the observed PFC population neuronal response. In 235 a previous study 18 , we demonstrated that the continuous (x,y) readout of a linear classifier assigning neuronal 236 activities to a spatial location of attention is a relevant proxy for a real-time access to the attentional spotlight 237 represented in the PFC. Importantly, this continuous (x,y) readout of the PFC attentional spotlight is predictive of 238 behavior, both in terms of hit and false alarm rates.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…As our study demonstrates the possibility of seamlessly decoding human top-down processes, if a further refined grid-shaped line array is developed and combined with a more elaborated classification method, a recent study74 provides advances in extending previous studies of decoding visuospatial attention6970717273, which were limited to decoding up to four discrete locations/classes. The authors found a neuronal signature of direct two-dimensional access to the spatial location of covert attention in macaque prefrontal cortex74. Together, these efforts in both externally triggered and internally driven manners may cooperatively open new perspectives to decoding technology in a multi-class and continuous mental representation space.…”
Section: Discussionmentioning
confidence: 74%